Izobraževanje o politiki v času permanentne negotovosti - Banjac, Marinko (Teorija in praksa, 2022)
The article addresses political education in its various forms in the context of the (neo)liberal socio-political order in which the emergence of depoliticisation and uncertainty is inherent. It shows how the prevailing systematisations and practices of education (including political ones) as well as political science interventions in the field of (political) education are caught in continuous attempts to eliminate uncertainty and the search for solutions entrapped within market rationalities and a liberal representative democracy. Based on Ranciere’s and partly Mouffe’s observation of politics and the political, the article offers a perspective that critically addresses these formations and processes and on this basis conceptualises political education that does not exclude but, on the contrary, takes uncertainty and social equality as a starting point. In this way, it offers an alternative form of political education as an always-already uncertain practice that stems from (in a Rancierian sense) radical equality and acts as a disruption to the existing consensual (neo)liberal order
Keywords: državljanska vzgoja; izobraževanje o politiki; negotovost; Politične vede; politološko izobraževanje; Vzgoja in izobraževanje